Management of government communication strategy in moving the new capital city in Indonesia from a public policy perspective - Saepudin, Eli Apud; Hartoko, Gatot; Kamilah, Fithrotul; Hidayat, Romi; Priatna, Achmad Nashrudin (Journal of Law Science, 2025)
The relocation of the national capital is a major project that requires public support, information transparency, and effective communication to overcome public resistance and ensure a good understanding of the policy objectives. Using a qualitative approach, this research examines the communication strategy implemented by the government through analysis of policy documents, communication media, and interviews with relevant parties. The results show that the government implements a communication strategy that includes socialization through mass media, direct outreach to the public, and the use of digital platforms to reach a wider audience. However, there are still obstacles such as negative public perception, limited access to information in certain areas, and uncertainty of project financing. This study recommends improvements in the quality and consistency of public communications, active community involvement in planning and implementation, and strengthening transparent policy messages to build trust and support the success of the IKN transfer.